Preparation of polyoxometalate compound (NH4)6(β-P2W18O62)/SiO2 by sol-gel method and its characterization - Osin Restinawaty Tambunan; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Preparation of polyoxometalate compound of (NH4)6(β-P2W18O62)nH2O supported with silica derived from the hydrolysis of tetraethyl orthosilicate by sol-gel method has been conducted. The compound was synthesized and characterized using FT-IR spectrophotometer, crystallinity using XRD analysis and the determination of acidity via quantitatively and qualitatively. Qualitative analysis was performed using ammonia and pyridine adsorption and quantitative analysis using potentiometric titration. FT-IR spectrum of (NH4)6(β-P2W18O62)nH2O appeared in wavenumber 786.96 cm-1 (W-OC-W), 918.12 cm-1 (W-Oe-W), 964.41 cm-1 (W=O), 1087.85 cm-1 (P-O), 3572.17 cm-1 (O-H), 1404.18 cm-1 (N-H) reinforced with wavenumber 1612.49 cm-1 with show vibration NH dari NH+, and to (NH4)6(β-P2W18O62)nH2O/SiO2 appears in wavenumbers 794.67 cm-1 (W-Oc-W), 918.12 cm-1 (W-Oe-W), 1049.28 cm-1 (W=O), 1087.85 cm-1 (P-O), 3564.15 cm-1 (O-H), 470.63 cm-1 (Si-O). Diffraction pattern of (NH4)6(β-P2W18O62)nH2O and (NH4)6(β-P2W18O62)nH2O/SiO2 compound show high crystanillity. The acidic properties showed (NH4)6(β-P2W18O62)nH2O/SiO2 more acidic than (NH4)6(β-P2W18O62)nH2O. Analysis of the effect of temperature on the stability of the compounds polyoxometalate (NH4)6(β-P2W18O62)nH2O/SiO2 show that the temperature of 600ºC the shift in wavenumbers of the compounds caused by vibration W=O, W-OC-W, W-Oe-W has been lost. This shows that at a temperatures of 600ºC on heating can cause changes in the structure of polyoxometalate (NH4)6(β-P2W18O62)nH2O/SiO2. Keywords : (NH4)6(β-P2W18O62).nH2O, Polyoxometalate, SiO2